POLIGAMI SEBAGAI RUKHSAH: ANALISIS KEADILAN DAN RELEVANSINYA DALAM FILSAFAT HUKUM ISLAM - Fauzul Kabir; Niken Retno Wulandari (Makkah: Journal Of Islamic Studies, 2025)
: In Islamic law, polygamy is not an absolute obligation or recommendation, but rather a dispensation (rukhsah) that is strictly regulated, with the primary condition being the ability to act justly. This article discusses polygamy from the perspective of Islamic legal philosophy by examining its normative basis in the Qur'an, specifically QS. An-Nisa: 3, which permits polygamy with up to four wives, emphasizing justice. The context of the revelation of this verse relates to the protection of the rights of orphans and widows after war. Analysis shows that although permitted, polygamy in practice often struggles to fulfill the essential condition of true justice, as affirmed in QS. An-Nisa: 129. The ruling on polygamy is conditional and must align with Maqāṣid al-Sharī'ah, which are to preserve the interests of religion, life, intellect, lineage, and property. In a contemporary context, polygamy tends to produce negative effects such as family conflict and injustice if not practiced with full responsibility. Therefore, polygamy should be understood as a limited option that may only be implemented when it truly fulfills the principles of justice and benefit.